Plasma Etching of Silk Fibroin: Experiments and Models. Issue 5 (13th March 2013) - Narayanamoorthy, Jayasri; Tsioris, Konstantinos; Omenetto, Fiorenzo G.; Hopwood, Jeffrey
Abstract: Silk fibroin biopolymer is anisotropically etched using oxygen and argon/oxygen plasma. At room temperature, silk removal rates are 0.25 µm min −1 . Scanning electron micrographs show that silk fibroin is a heterogeneous material for which plasma etching reveals a silk backbone structure as the matrix is more quickly volatilized. A simple physical model of silk etching accurately predicts the etch rate without any fitting parameters. The model and experimental data show that atomic oxygen, in the absence of ion bombardment, only slowly etches silk (<0.017 µm min −1 ) and does not spontaneously etch silk fibroin backbone structures. Rather, the silk constituents must be removed by first covering the surface with adsorbed atomic oxygen which is then simultaneously desorbed through energetic ion bombardment. Abstract : Silk fibroin, a protein biopolymer has proven utility for biomedical high technology applications. Patterning silk fibroin on the micro‐ and nano‐scale has increased this biopolymer's functionality. Plasma etching in particular is a versatile tool to provide the precise formation of structures on this length scale. For the first time, a detailed quantification and modeling of plasma processing parameters and their effects on the biopolymer silk fibroin are presented in this report.